Frequency dependent ultrasonic attenuation coefficient assessment in fresh tissue - O'BRIEN, W. D.; SEGAL, L. A. (Archives of Acoustics, 1984)
The authors discuss the frequency dependent ultrasonic attenuation coefficient for fresh liver and fresh spleen from bovine, porcine and lamb, and fresh pancreas from bovine and futher discuss the role of these attenuation coefficients in terms of their collagen, actually hydroxyproline, concentration. The technical procedures of specimen handling and data gathering are reproducible. A higher order fit appears to be necessary for describing the frequency dependency of the attenuation coefficient. There does not appear to be any correlation between the attenuation coefficient and collagen concentration for these tissues.